A case of mimicking angioedema： chin silicone granulomatous reaction spreading all over the face after receiving liquid silicone injection forty years previously - Chen, Yu-Cheng; Chen, Mei-Ling; Chiu, Ying-Ming (Chinese medical journal, 2011)
Liquid injectable silicone has been used for soft tissue augmentation for five decades. Many complications following liquid silicone injection have been reported. To diagnose and manage silicone granuloma remains difficult. Silicone granuloma must be diagnosed with the history of liquid silicone injection and the histology of tissue biopsy. We presented a case of granulomatous reaction after the injection of liquid silicone for chin augmentation forty years ago, causing total facial swelling, which mimicking angioedema initially. We administered methylprednisolone to the patient. Initial response to methylprednisolone was favorable.